The Role of Islamic Psychospiritual in Building Self-Resilience of Cancer Caregivers - Norwahizatul wahed; Che Zarrina Sa`ari; Mohd Syukri Zainal Abidin; Siti Sarah Ahmad; Syed Mohammad Hilmi (International Journal of Nusantara Islam, 2023)
The global community is increasingly recognizing the integration of health science with religion and spirituality. In Malaysia, the field of Islamic psychospiritual science, which combines psychology with spirituality and Islamic teachings, has garnered significant research attention, particularly in addressing the challenges faced by cancer caregivers. These caregivers, often referred to as "hidden patients," experience a range of difficulties including physical, emotional, spiritual, social, and financial burdens that adversely affect their quality of life. However, society tends to prioritize the health and well-being of the patients over that of the caregivers. In reality, caregivers place the needs of the patients above their own in all aspects. Spiritual, religious, and emotional distress are prevalent concerns for both patients and caregivers during the crisis of cancer, which is often associated with mortality. Hence, the objective of this article is to explore the role of Islamic psychospiritual knowledge in supporting cancer caregivers, specifically in addressing their spiritual, religious, and emotional well-being. The data collection process utilizes library methods based on key findings from previous studies, while data analysis is conducted using a thematic analysis approach. The findings of this study indicate that religious aspects emphasized in Islamic psychospiritual disciplines can enhance caregivers' resilience in effectively managing various cancer-related challenges, thereby improving their overall quality of life. Hence, the significance of the spiritual and religious dimension, which acts as a protective factor, should not be disregarded. Lastly, this article proposes the provision of spiritual and religious educational materials within medical settings as valuable resources for cancer caregivers to reinforce their own well-being.